2022
DOI: 10.3389/fped.2022.877200
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Nomogram for Clinical Risk Prediction of Preterm Neonate Death in Ethiopia

Abstract: IntroductionIn 2020, over 6,500 newborn deaths occured every day, resulting in 2.4 million children dying in their 1st month of life. Ethiopia is one of the countries that will need to step up their efforts and expedite progress to meet the 2030 sustainable development goal. Developing prediction models to forecast the mortality of preterm neonates could be valuable in low-resource settings with limited amenities, such as Ethiopia. Therefore, the study aims to develop a nomogram for clinical risk prediction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Patel et al ( 44 ) reported that RDS was the leading cause of in-hospital death among EPIs with a GA of 24–27 weeks. Another predictive models also reported RDS as a critical indicator for the prognoses of preterm infants, especially in underdeveloped countries ( 45 ). Pulmonary hemorrhage and shock are prognostic determinants.…”
Section: Discussionmentioning
confidence: 94%
“…Patel et al ( 44 ) reported that RDS was the leading cause of in-hospital death among EPIs with a GA of 24–27 weeks. Another predictive models also reported RDS as a critical indicator for the prognoses of preterm infants, especially in underdeveloped countries ( 45 ). Pulmonary hemorrhage and shock are prognostic determinants.…”
Section: Discussionmentioning
confidence: 94%